Perturbation Analysis for Solutions of Algebraic Riccati Equations (Journal of Computational Mathematics, 2021)
This paper discusses the conditioning of algebraic Riccati equations, i.e. the influence of perturbations in data on the positive semi-definite solution. A perturbation bound for the solution is given.